The ancestral duplicated DL/CRC orthologs, PeDL1 and PeDL2, function in orchid reproductive organ innovation - Chen, You-Yi; Hsiao, Yu-Yun; Li, Chung-I; Yeh, Chuan-Ming; Mitsuda, Nobutaka; Yang, Hong-Xing; Chiu, Chi-Chou; Chang, Song-Bin; Liu, Zhong-Jian; Tsai, Wen-Chieh (Journal of experimental botany, 2021)
PeDL1 and PeDL2 are involved in orchid gynostemium and ovule development and provide insights into the evolution of orchid reproductive organ development. Abstract Orchid gynostemium, the fused organ of the androecium and gynoecium, and ovule development are unique developmental processes. Two DROOPING LEAF/CRABS CLAW (DL/CRC) genes, PeDL1 and PeDL2, were identified from the Phalaenopsis orchid genome and functionally characterized. Phylogenetic analysis indicated that the most recent common ancestor of orchids contained the duplicated DL/CRC-like genes. Temporal and spatial expression analysis indicated that PeDL genes are specifically expressed in the gynostemium and at the early stages of ovule development. Both PeDLs could partially complement an Arabidopsis crc-1 mutant. Virus-induced gene silencing (VIGS) of PeDL1 and PeDL2 affected the number of protuberant ovule initials differentiated from the placenta. Transient overexpression of PeDL1 in Phalaenopsis orchids caused abnormal development of ovule and stigmatic cavity of gynostemium. PeDL1, but not PeDL2, could form a heterodimer with Phalaenopsis equestris CINCINNATA 8 (PeCIN8). Paralogous retention and subsequent divergence of the gene sequences of PeDL1 and PeDL2 in P. equestris might result in the differentiation of function and protein behaviors. These results reveal that the ancestral duplicated DL/CRC-like genes play important roles in orchid reproductive organ innovation.